2007
DOI: 10.1529/biophysj.106.096982
|View full text |Cite
|
Sign up to set email alerts
|

Free Energy of Membrane Protein Unfolding Derived from Single-Molecule Force Measurements

Abstract: Mechanical single-molecule techniques offer exciting possibilities to investigate protein folding and stability in native environments at submolecular resolution. By applying a free-energy reconstruction procedure developed by Hummer and Szabo, which is based on a statistical theorem introduced by Jarzynski, we determined the unfolding free energy of the membrane proteins bacteriorhodopsin (BR), halorhodopsin, and the sodium-proton antiporter NhaA. The calculated energies ranged from 290.5 kcal/mol for BR to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 48 publications
5
44
4
Order By: Relevance
“…In other words, it should be in the stalk region or transmembrane helix of GPIba. The force required to unfold a transmembrane helix is much stronger (.100 pN) 42,43 than what was observed here (;10 pN). In addition, unfolding of the 25-residue transmembrane helix of GPIba would have produced an unfolding contour length of ;10 nm, much shorter than .20 nm observed in the force curves ( Figure 2C).…”
Section: Localization Of Msd To the Stalk Region Of Gpibacontrasting
confidence: 55%
“…In other words, it should be in the stalk region or transmembrane helix of GPIba. The force required to unfold a transmembrane helix is much stronger (.100 pN) 42,43 than what was observed here (;10 pN). In addition, unfolding of the 25-residue transmembrane helix of GPIba would have produced an unfolding contour length of ;10 nm, much shorter than .20 nm observed in the force curves ( Figure 2C).…”
Section: Localization Of Msd To the Stalk Region Of Gpibacontrasting
confidence: 55%
“…[85][86][87] By applying Jarzynski's equality it was found that the equilibrium folding and insertion energies of the membrane proteins range from % 160 kcal mol À1 (for bacteriorhodopsin and halorhodopsin) to % 280 kcal mol À1 (for NhaA). [88] As expected for equilibrium properties, these energies are force-loading rate-independent, that is, they do not depend on how far from equilibrium the experiment was performed. Remarkably, the average free energy for unfolding and extracting single amino acids is essentially the same for all three membrane proteins (%0.70 kcal mol…”
Section: Determining Insertion and Folding Energies By Using Jarzynskmentioning
confidence: 57%
“…A sequence-dependent comparison with the biophysical and biological hydrophobicity scales introduced by White and Wimley [89] and Hessa et al [90] indicate that these energies contain hydrophobic interactions and contributions from hydrogen bonds. [88] Additionally, the Jarzynski analysis reveals heterogeneous energetic properties of individual transmembrane a-helices and a-helical segments. The unfolding pathways of halorhodopsin resemble those of bacteriorhodopsin except for one difference-halorhodopsin exhibits an additional pi-bulk interaction that splits its a-helix E into two structurally distinct segments.…”
mentioning
confidence: 99%
“…unfolding of 90 k B T or 53 kcal·mol −1 was derived, similar to helix-hairpins in bacteriorhodopsin (29). Certainly this solidity constitutes a prerequisite for holding the pigments precisely in space for light-harvesting function.…”
Section: Resultsmentioning
confidence: 83%